Uma contribuição ao processo do compartilhamento de responsabilidades sobre as distorções harmônicas via chaveamento de unidades capacitivas - Santos, Andréia Crico dos (2015)
Among the points that deserve recognition in the context of Electric Power Quality area related to the harmonic distortions is the issue of responsibilities assignment. In fact, given significant levels of harmonic distortions where at a particular point or along a specific measurement bus, the importance of knowing the percentages of responsibility to be assigned to the parties involved becomes clear when it is necessary to implement mitigation measures, such as the installation of harmonic filters. In this case, it is desirable to use a systematic and reliable procedure that culminate in a consensus on the financial responsibility associated with mitigation process. The literature presents some procedures that propose the allocation of responsibility for harmonic distortion, but previous studies have sought to highlight difficulties related to inherent weaknesses to the proposed developments or infeasibility practices. Among these methodologies deserves attention the principle of Superposition that, despite consistent development, has limited application due to the need for prior knowledge of the harmonic impedances of the agents involved. The values of these impedances, especially consumer part, it is not an information easily obtained. Inserted in this context, this work presents a proposal which seeks to contribute to the process of responsibility assignment on harmonic distortions using capacitor units switching. This technique aims to provide consistent information on the harmonic impedances of a consumer unit for the application of superposition principle aforementioned.